2012
DOI: 10.4103/2279-042x.108373
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical care for asthma patients: A Developing Country′s Experience

Abstract: Objective:This study aims at the outcome of providing pharmaceutical care service for asthma patients through an active partnership between clinical pharmacist and patients, for an optimal pharmacotherapy and a better quality of life (QoL).Methods:In this controlled clinical trial, which was conducted for 8 months (2009) in the Institute of Pulmonary Medicine and Research Centre of a 550-bedded multispecialty tertiary care teaching hospital in India, all patients diagnosed with asthma at least 6 months before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 20 publications
0
29
0
3
Order By: Relevance
“…The randomised control trials (RCTs) were conducted between 1995 and 2016; four South Asian trials were from India (labelled ‘majority’ South Asian), 30 33 four South Asian trials were from the UK 34 36 and one from Canada 37 (labelled ‘minority’ South Asian), and nine African-American trials were from the USA (labelled ‘minority’ African American) 26 34 (see Table 2 ). The overall risk of bias within trials was uncertain, 30 , 33 , 37 41 or high. 31 , 32 , 36 , 42 45 Three trials had low risk 34 , 35 , 46 (see Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The randomised control trials (RCTs) were conducted between 1995 and 2016; four South Asian trials were from India (labelled ‘majority’ South Asian), 30 33 four South Asian trials were from the UK 34 36 and one from Canada 37 (labelled ‘minority’ South Asian), and nine African-American trials were from the USA (labelled ‘minority’ African American) 26 34 (see Table 2 ). The overall risk of bias within trials was uncertain, 30 , 33 , 37 41 or high. 31 , 32 , 36 , 42 45 Three trials had low risk 34 , 35 , 46 (see Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…drug administration Trained social scientist (-) Group; Modified Patients; Parents; 10–45; 276 (140/136) Daily diary (included symptom assessment and financial workbook) Written material Asthma therapy PAAPs /four 2 hour sessions Shanmugam 33 India Provided pharmaceutical care through partnership of pharmacists and patients for good asthma control Indian Tertiary (university hospital) Education; sessions, asthma care diary in English and Tamil (including leaflet), PAAP and symptom log sheet No pharmaceutical care Not stated (English and Tamil) Written material; Modified Patients Age; −; 66 (33/33) Medication counselling/not stated Other methods not stated ‘Minority’ South Asians trials Griffiths 34 UK Tested whether specialist nurses across ethnically diverse and deprived areas reduce unscheduled care South Asians (mostly Bangladeshi) White Caucasians, Other (Black/African Caribbean/Other) Primary/secondary (out-of-hours GP service/hospital) Education; training based on guidelines, nurse review with advice Usual care; single nurse visits to discuss asthma guidelines and check inhaler technique Trained nurse specialists (partially; PAAPs explained in Sylheti) Individual; Modified PAAP explained in English and Sylheti Written material; Ongoing clinical support for professionals on computer prompts Patients; 4–60; 164 (95/69) Deprived/urban Peak flow meters provided Telephone Oral corticosteroids/2 one hour visits for GP practices; 194 days Griffiths 35 UK Tested whether culturally specific education programmes adapted from USA interventions reduce unscheduled care South Asians (Bangladeshi, Pakistani, Indian, Sri Lankan) Primary (GP) Education; session including PAAP, nurse follow-ups to book appointments (CDSMP), research training with video based on guidelines, South Asian actors and manualised programme (PACE)/PACE; two seminars; CDSMP; 2-ho...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6,[13][14][15] Patient support programs, such as medication management and counseling, have the potential to improve patient's disease control and medication adherence. 16,17 A previous pharmacist intervention study has shown a positive impact on patients' knowledge about asthma and medication. 18 Other studies have shown that pharmacist interventions were effective in improving the inhaler device technique skills, 19,20 and a randomized controlled trial demonstrated that pharmacist interventions improved both medication adherence and inhaler device technique in patients with chronic obstructive pulmonary disease (COPD).…”
Section: Introductionmentioning
confidence: 99%